Kurikulum Terintegrasi di Pondok Pesantren Annida Al Islamy Bekasi - Mursyidi, Wathroh (Almarhalah | Jurnal Pendidikan Islam, 2018)
The institution of education that allows for formal, informal, even non formal learning is also a boarding school. In its history, the direct correlation between the boarding schoool, families and communities and even the state has been going on for four centuries. One thing the boarding school then needs is to formulate a clear curriculum that can cover all forms and educational environment. The boarding school of Annida Al Islamy Bekasi is one of the oldest educational institutions in the city of bekasi, locatedÂ  in center of bekasi That still tries to keep up the boarding school tradition by adjusting the needs of the globalization era. Â For one thing, by undertaking the integration of the educational system in particular terms of developing the curriculum. Through the curriculum it is expected to contribute to the education effort for individuals to become humans and to become ulul al baab generation, fostered, guided, and condemned with syari 'at and kaidah-based islamic by the kiai, asatidz, and the masters at boarding school with the highlighted character of Islam as rahmatan lil 'aalamin.